Fiscal and Monetary Policy Synergy in Support of Indonesia's Macroeconomic Stability - Sri Dewi Yusuf; Rismanto Rismanto (COMPETITIVE, 2025)
The synergy between fiscal and monetary policy plays an important role in supporting Indonesia's macroeconomic stability. Fiscal policy, which includes the management of the state budget and government spending, and monetary policy, which is managed by the central bank through the regulation of the money supply and interest rates, share the goal of maintaining economic stability. This study aims to explore the interaction between the two policies and analyze how synergies between them can promote sustainable economic growth. In crisis situations such as the COVID-19 pandemic, expansionary fiscal policy and appropriate monetary intervention play an important role in boosting aggregate demand, controlling inflation, and maintaining currency stability. Effective coordination between government and central bank actions is key in facing domestic and global challenges to create a resilient and stable economy.